Cross-neutralization and viral fitness of SARS-CoV-2 Omicron sublineages - Hongjie Xia; Jason Yeung; Birte Kalveram; Cody J. Bills; John Yun-Chung Chen; Chaitanya Kurhade; Jing Zou; Steven G. Widen; Brian R. Mann; Rebecca Kondor; C. Todd Davis; Bin Zhou; et al. (Emerging Microbes and Infections)
The rapid evolution of SARS-CoV-2 Omicron sublineages mandates a better understanding of viral replication and cross-neutralization among these sublineages. Here we used K18-hACE2 mice and primary human airway cultures to examine the viral fitness and antigenic relationship among Omicron sublineages. In both K18-hACE2 mice and human airway cultures, Omicron sublineages exhibited a replication order of BA.5 ≥ BA.2 ≥ BA.2.12.1 > BA.1; no difference in body weight loss was observed among different sublineage-infected mice. The BA.1-, BA.2-, BA.2.12.1-, and BA.5-infected mice developed distinguishable cross-neutralizations against Omicron sublineages, but exhibited little neutralization against the index virus (i.e. USA-WA1/2020) or the Delta variant. Surprisingly, the BA.5-infected mice developed higher neutralization activity against heterologous BA.2 and BA.2.12.1 than that against homologous BA.5; serum neutralizing titres did not always correlate with viral replication levels in infected animals. Our results revealed a distinct antigenic cartography of Omicron sublineages and support the bivalent vaccine approach.